2020
DOI: 10.1002/hed.26330
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus in oral epithelial dysplasia: Systematic review and meta‐analysis

Abstract: The purpose of this systematic review and meta‐analysis was to estimate the overall and type‐specific prevalence of human papillomavirus (HPV) DNA in oral epithelial dysplasia and assess p16INK4a overexpression in relation to HPV‐status. A systematic literature search identified 31 eligible studies (832 cases) evaluating the presence of HPV DNA in oral epithelial dysplasia cases by PCR. Of these, six studies evaluated p16INK4a overexpression in relation to HPV‐status. The overall pooled prevalence of HPV DNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…was type 16 (de laCour et al, 2020). These prevalence figures seem high when compared to rarity of HPV-dysplasia confirmed by in situtechniques and are probably an overestimate.…”
mentioning
confidence: 77%
“…was type 16 (de laCour et al, 2020). These prevalence figures seem high when compared to rarity of HPV-dysplasia confirmed by in situtechniques and are probably an overestimate.…”
mentioning
confidence: 77%
“…40,41 There was a low prevalence of HPVOED in this cohort (2.3%) compared with the 27.2% published in a recent meta-analysis on prevalence of HPV in OED. 42 The high prevalence values in the studies included in the meta-analysis could be due to the use of polymerase chain reaction (PCR)-based techniques as the method to detect HPV DNA. PCR-based methods though sensitive, lack specificity and may give a positive result even if the virus was not transcriptionally active (carrier/bystander).…”
Section: Discussionmentioning
confidence: 99%
“…These molecular changes are commonly detected in dysplastic epithelial cells [ 136 , 137 ], which are also more susceptible to EBV infection [ 116 ]. Interestingly, the pooled prevalence of HPV infection was 27.2% in oral epithelial dysplasia [ 138 ], whereas other authors found a 50% positivity in oral cavity and oropharyngeal dysplasia [ 139 ]. Guidry and Scott (2018) reported a significant reduction in EBV DNA replication in both HPV-positive and E7-immortalized human keratinocytes when compared with the EBV DNA replication observed in primary keratinocytes cultured in organotypic rafts [ 140 ], suggesting the contribution of HPV to the establishment of EBV latency.…”
Section: Possible Mechanisms Of Hr-hpv/ebv Cooperationmentioning
confidence: 99%